Komitmen Organisasi sebagai Pemediasi Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior - Apriliyanto, Yohanes Angga; Agus Sugiarto (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This research examines the effect of organizational commitment as a mediating variable factor on cultural organization and job satisfaction about organizational citizenship behavior. Method: The data analysis uses Partial Least Square Structural Equation Modeling (PLS-SEM) bootstrapping. Research Finding: The result of the research showed that culture organization has a significant impact on organizational citizenship behavior, job satisfaction does not significant affect organizational citizenship behavior, culture organization significantly affect organizational commitment, job satisfaction has a significant effect on organizational commitment, commitment organizational does not significant affect organizational citizenship behavior, organizational commitment does not mediate the influence of culture organization on organizational citizenship behavior, and organizational commitment does not mediate the influence of job satisfaction on organizational citizenship behavior. Theoretical contribution: The conceptual framework developed in this research model is a development of previous research by presenting organizational commitment as a mediator variable on culture organization and job satisfaction toward organizational citizenship behavior. Practical Implication: The results of this research are a reference for companies in maintaining and increasing the level of organizational citizenship behavior of employees and maintaining the level of employee loyalty to the company. Research Limitation: This research focuses on one company with a relatively small number of employees so it can’t represent other companies operating in the same field.